2005
DOI: 10.1002/uog.1997
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional sonographic description of the fetal frontal bones and metopic suture

Abstract: Objective To describe the morphology of the frontal bones and metopic suture at 9-34 weeks of gestation using three-dimensional (3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 13 publications
(11 reference statements)
1
64
1
4
Order By: Relevance
“…In the three-dimensional sonographic description of normal fetal frontal bones and the metopic suture, Faro et al reported the presence of a progressive radial bone expansion in the second trimester, and the closure of the metopic suture starting from the glabella and moving toward the anterior fontanel in the third trimester (5). Similarly, in the threedimensional sonographic description of an abnormal metopic suture in second and third trimester fetuses, Chaoui et al reported pathological changes in the metopic suture of 11 fetuses at 17 to 32 weeks.…”
Section: █ Discussionmentioning
confidence: 99%
“…In the three-dimensional sonographic description of normal fetal frontal bones and the metopic suture, Faro et al reported the presence of a progressive radial bone expansion in the second trimester, and the closure of the metopic suture starting from the glabella and moving toward the anterior fontanel in the third trimester (5). Similarly, in the threedimensional sonographic description of an abnormal metopic suture in second and third trimester fetuses, Chaoui et al reported pathological changes in the metopic suture of 11 fetuses at 17 to 32 weeks.…”
Section: █ Discussionmentioning
confidence: 99%
“…Reports on prenatal ultrasound examination of cranial sutures are relatively rare in the literature [2,[11][12][13] and the detection rates of craniosynostosis are low [14,15]. A retrospective study including 618 cases of isolated craniosynostosis revealed that only 2 cases (0.3%) were known to have been diagnosed prenatally [16].…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…Special attention should be paid to fetal hands and feet, long bone growth, central nervous system and heart [3]. The evaluation of fetal head, face and sutures can be complemented by 3D ultrasound [11,13,24]. A report has shown that 3D ultrasound revealed diagnostic features of Apert syndrome, such as wide metopic suture and absent coronal sutures earlier than 2D ultrasound [25].…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…The visualization of fetal cranial sutures with the help of 3D ultrasound has been the aim of many studies: [13][14][15][16][17][18][19][20][21][22] surface rendering combined with the transparent maximum mode enables visualization of the progressive ossification of skull bones and the onset of fusion of frontal bones (Figs 3 and 4).…”
Section: Three-dimensional Ultrasound: Technical Aspects and Clinicalmentioning
confidence: 99%